Knowledge, Attitudes and Practices regarding acute Bartonellosis (Oroya fever`s) in Persons Living in Ollantaytambo District, Urubamba Province in the Sacred Valley of the Incas, Cusco, Peru - Castillo Schilder, Castillo Schilder (2018)
Introduction: Bartonellosis is a prevalent disease in Andean valleys of Peru, typically in endemic areas such as Ancash, Cajamarca, Junín, and Amazonas. However, in the past few years, new endemic areas have been identified, such as the Sacred Valley of the Incas in Cusco. Objective: To describe knowledge, attitude and practices regarding Bartonellosis in persons living in Ollantaytambo District, Urubamba Province in the Sacred Valley of the Incas, Cusco-Peru, July 2004. Materials and Methods: A knowledge, attitude and practices (KAP) survey was conducted in 280 persons from ten communities identified as being at risk for Bartonellosis in Ollantaytambo. A score was used to identify knowledge levels in three categories. Results: We found that 151/280 persons (53.94%) had advanced (level III) knowledge, that in case of feeling sick, 228/242 (94.21%) residents would go to the health care center, and that 32.02% (92/242) do not practice any activity to prevent Bartonellosis. Conclusions: More than half of people living in the surveyed areas adequately recognize basic aspects regarding Bartonellosis and the vector involved in its transmission. Most people do not know preventive measures against; therefore, they do not practice such activities. However, they have a favorable attitude for preventing the disease.